1990
DOI: 10.1002/ajp.1350220406
|View full text |Cite
|
Sign up to set email alerts
|

Primate origins: Lessons from a neotropical marsupial

Abstract: The didelphid Caluromys shows evolutionary convergence towards prosimians in having a relatively large brain, large eyes, small litters, slow development, and agile locomotion. The selection pressures that favored the emergence of primate-like traits in Caluromys from a generalized didelphid ancestor may be analogous to the selection pressures favoring the initial divergence of primates from a primitive nonprimate ancestor, and thus Caluromys provides an independent test of the arboreal hypothesis Primates, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 27 publications
(13 reference statements)
5
117
1
Order By: Relevance
“…Several recent accounts 64,102,114 suggest that the features that distinguish primates from other mammals today originated through a gradual accretion of small adaptive changes, producing a cascade of more and more concentrically arranged taxa with smaller and smaller clusters of less and less important synapomorphies (Fig. 5), just as we saw in the early mammals.…”
Section: Primate Origins?supporting
confidence: 58%
“…Several recent accounts 64,102,114 suggest that the features that distinguish primates from other mammals today originated through a gradual accretion of small adaptive changes, producing a cascade of more and more concentrically arranged taxa with smaller and smaller clusters of less and less important synapomorphies (Fig. 5), just as we saw in the early mammals.…”
Section: Primate Origins?supporting
confidence: 58%
“…Because the fine-branch environment has often been cited as the fundamental niche of early primates (e.g. Cartmill, 1972;Rasmussen, 1990;Sussman et al, 2013), investigating the precise mechanical demands of moving on supports that are both narrow and compliant is critical to understanding primate locomotor adaptation and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have, therefore, emphasised the importance of studying the behaviour and ecology of small arboreal mammals in reconstructing the early evolution of primates and understanding the functional significance of special morphological adaptations (LeGros Clark, 1959;Cartmill, 1972;Martin, 1972;Cartmill, 1974;Jenkins, 1974;Rasmussen, 1990;Gebo, 2004;Sargis et al, 2007). Various locomotor studies have shown that small mammals display a high level of similarity in their locomotor kinematics and limb proportions independent of phylogeny and locomotor habitat (Jenkins, 1971;Fischer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%